EMA on Firm Value: A Moderating Role Of Firm Performance - Rahmazaniati, Linda; Rahmadani, Ika; Vonna, Sari Maulida; Maulina, Rina; Husen, Tamitha Intassar; Restya, Winda Putri Diah; Harahap, Septiana Dian Hatami (Universitas Serang Raya, 2025)
This study aims to examine the effect of EMA on firm value: a moderated role of firm performance. The population in this study are palm oil companies listed on the Indonesia Stock Exchange. The sample selection in this study used a purposive sampling method which was obtained a 10 sample of oil palm companies with 3 years of observation. The data analysis was conducted using Eviews 12, and the findings indicate that Exponential Moving Average (EMA) does not exert any impact on firm value. Additionally, it was observed that firm performance exhibits a noteworthy negative influence on the correlation between EMA and firm value.